Study of vehicle ownership for urban and rural households in India. (January 2017) - Choudhary, Ravi; Vasudevan, Vinod
Abstract: Private vehicle ownership has been growing in double digits over the last decade. This paper examines the factors determining vehicle ownership for urban and rural households in India. Separate nation-wide disaggregate vehicle ownership models for urban and rural areas in India are developed using readily available consumer expenditure survey dataset. A consumption based proxy variable is assumed to represent economic standard of households. Comparison between vehicle ownership behavior of urban and rural households show that rural households are more inclined to own private vehicle than urban households with same economic standards. Amongst households with regular salaried members, rural households' preference to own two wheelers is greater than that of urban households. While the presence of elderly member or children is considered, urban households showed more preference to own four-wheeler than rural households. As a first nation-wise study to understand the differences in vehicle ownership behavior in urban and rural areas of India, this study provides a lot of useful insights which could be valuable to various stakeholders.